Relayout dan Pengurangan Waktu Siklus sebagai Solusi Peningkatan Produktivitas UMKM Pembuatan Minuman Herbal KUPS Etnobotani melalui Kegiatan Pengabdian - Amelia Amir; Heru Alimudin Yahya; Muhammad Rizky Deaz Ramadhan; Zulfadli; Dessi Mufti (LPPI UMN AL WASHLIYAH, 2025)
This community service program was designed to optimise of the flow materials, intermediate products, and finished products in the herbal drink processing enterprise managed by the Social Forestry Business Group Padusi Etnobotani in Lambung Bukit, Batu Busuak, Padang City. The intervention sought to shorten the workflow, reduce waiting time, and enhance both work convenience and labour productivity. Activities comprised structured counselling and hands-on mentoring on facility layout improvement in a production kitchen measuring four by two point five metres. The stages included mapping the production sequence using a process flow diagram, measuring the time and distance of material handling, analysing activity relationships, redesigning the facility layout, and designing a multifunction workbench for washing, draining, and cutting raw materials. The initial assessment revealed an elongated process flow with four material transfers, backtracking movements, and a non-hygienic washing area located outside the production room. Implementation of the proposed layout consolidated all main activities within a single room, eliminated backtracking, reduced transportation time from 50 to 10 minutes, and decreased cycle time from 760 to 720 minutes. These improvements enhanced hygiene conditions, ergonomic comfort, and the potential output per production period, thereby strengthening the competitiveness and sustainability of the herbal drink enterprise based on protected forest resources.